Widespread bacterial lysine degradation proceeding via glutarate and L-2-hydroxyglutarate. Issue 1 (December 2018) - Knorr, Sebastian; Sinn, Malte; Galetskiy, Dmitry; Williams, Rhys; Wang, Changhao; Müller, Nicolai; Mayans, Olga; Schleheck, David; Hartig, Jörg
Abstract Lysine degradation has remained elusive in many organisms includingEscherichia coli . Here we report catabolism of lysine to succinate inE. coli involving glutarate andL -2-hydroxyglutarate as intermediates. We show that CsiD acts as an α-ketoglutarate-dependent dioxygenase catalysing hydroxylation of glutarate toL -2-hydroxyglutarate. CsiD is found widespread in bacteria. We present crystal structures of CsiD in complex with glutarate, succinate, and the inhibitor N-oxalyl-glycine, demonstrating strong discrimination between the structurally related ligands. We show thatL -2-hydroxyglutarate is converted to α-ketoglutarate by LhgO acting as a membrane-bound, ubiquinone-linked dehydrogenase. Lysine enters the pathway via 5-aminovalerate by the promiscuous enzymes GabT and GabD. We demonstrate that repression of the pathway by CsiR is relieved upon glutarate binding. In conclusion, lysine degradation provides an important link in central metabolism. Our results imply the gut microbiome as a potential source of glutarate andL -2-hydroxyglutarate associated with human diseases such as cancer and organic acidurias. Lysine degradation and the role of the metabolites glutarate andL -2-hydroxyglutarate have remained elusive in many organisms includingEscherichia coli . Here authors present a pathway for catabolism of lysine to succinate inE. coli involving glutarate andL -2-hydroxyglutarate as intermediates.